Extreme nonequilibrium synthesis of a Ca–Cu–Si clathrate during the Trinity nuclear test - Luca Bindi; Marek Mihalkovič; Michael Widom; Paul J. Steinhardt (Proceedings of the National Academy of Sciences, 2026)
The Trinity nuclear test of July 16, 1945, generated extreme transient conditions that produced trinitite, a silicate glass containing rare metallic phases. Here we report the discovery and structural and chemical characterization of a previously unknown Ca–Cu–Si type-I clathrate, (Ca 3.3 Cu 0.4 Fe 0.3 ) Σ=4 Si 23 , identified within a Cu-rich metallic droplet embedded in red trinitite. Single-crystal X-ray diffraction shows that this phase adopts the cubic clathrate-I topology, representing the first crystallographically confirmed clathrate structure documented among the solid-state products of a nuclear explosion. Beyond its intrinsic significance, this phase is notable for its close contextual association with the previously reported Si-rich icosahedral quasicrystal formed in the same detonation. Both phases formed under identical extreme conditions, occur within similar Cu-rich droplets, and share an unusually Si-rich Ca–Cu–Si–(Fe) chemistry, motivating an evaluation of whether the quasicrystal could be structurally derived from a clathrate framework. To evaluate this possibility, we performed density functional theory calculations on clathrate-based icosahedral models across a range of Cu contents. The results indicate that clathrate-derived icosahedral structures are mechanically plausible and metastable at low Cu concentrations (~10 to 11%) but become unstable as Cu content approaches that of the Trinity quasicrystal. These findings constrain viable structural models for the quasicrystal and argue against a simple clathrate-derived interpretation.